PENGARUH MODEL PEMBELAJARAN PROYEK MATEMATIKA MISSOURI (PMM) TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA KELAS V SDN 10 MATARAM - Nurul Amiraj; Harry Soperijanto; I Nyoman Karma; Husniati Husniati; Heri Hadi Saputra (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2020)
This study aims to determine the influence of the missouri mathematics project learning model (PMM) to mathematically creative thinking in grade 5 students of elementary school 10 Mataram academic year 2019/2020. The type of research used is Pre-Experimental Designs in the form of One-Group Pretest-Posttest. The subjects used were 36 grade 5 A students of elementary school 10 Mataram academic year 2019/2020. The type of research used is Pre-Experimental 10 Mataram. The techniques used for data collection are observation and tests. The data obtained were analyzed by sample related T-test with a confidence level of 95% at a significance level of 5%. But first the Normality test is done using the Chi-Square test, the significance value of the pretest is 5.72 ≤ 11.070 and the significance value of the posttest is 5.72 ≤ 11.070 so that the data is normally distributed. Based on the results of statistical calculations T-test related samples obtained tcount value of 11.672 and ttable of 1.994 so the results of tcount ≥ ttable that is equal to 11.672 ≥ 1.994. So from the results of the hypothesis test shows H0 is rejected and Ha is accepted, which means there is an of the missouri mathematics project learning model (PMM) to mathematically creative thinking in grade 5 students of elementary school 10 Mataram academic year 2019/2020. The type of research used is Pre-Experimental 10 Mataram in academic year 2019/2020. The magnitude of the influence of the missouri mathematics project learning model (PMM) to mathematically creative thinking is known by using the Effect Size calculation obtained ES Price results (1.48)> 1.2: in the relatively high category.